Optimization of the Process for Processed Cheese Made from Milk Powder Rich in γ-Aminobutyric Acid and Analysis of Its Antihypertensive Activity - Biqi LIU; Jiayue WANG; Qinggang XIE; Chaoxin MAN; Yujun JIANG; Yuehui NING; Xinyan YANG; Ling GUO (Shipin gongye ke-ji)
This study aimed to develop a functional processed cheese rich in γ-aminobutyric acid (GABA) and evaluate its antihypertensive activity. Fresh cheese was prepared using whole milk powder as the raw material, and the reprocessing technology was optimized, including the amounts of stabilizers and emulsifying salts, emulsifying temperature, and stirring speed. The effects of these factors on the texture, rheological, and sensory characteristics of the processed cheese were analyzed. The physicochemical properties, GABA content, and angiotensin-converting enzyme (ACE) inhibition rate of the processed cheese produced under optimal conditions were also evaluated. The results showed that after ripening for 7 d at 25 ℃, GABA synthesis, Glu degradation, and lactic acid bacteria growth all performed excellently, with the highest GABA content in the cheese reaching 3.60 mg/g. Through response surface optimization, the optimal formulation was determined: Stabilizer at 2.22%, emulsifying salt at 1.72%, emulsification temperature at 75 ℃, and stirring speed at 4137 r/min. The processed cheese prepared using this optimal formulation exhibited balanced nutritional content, with a firm texture and strong cohesiveness. The GABA content was 2.01 mg/g, and the ACE inhibition rate was 30.30%, demonstrating strong antihypertensive potential.